Nanostructured scaffold for neural tissue regeneration - Abbas, Walaa (AUC Knowledge Fountain, 2018)
Neural regeneration treatment after spinal cord injury (SCI) is still unsatisfactory despite the advances made in the field. One of the main challenges in neural tissue engineering is the axonal growth and directionality. Cell and molecular therapies can enhance the axonal attachment and growth. However, axons may be unsuccessful to maintain their native organization and may grow in a disorganized fashion. Nanofiber scaffolds represent a potential solution for the problem of nerve regeneration and axon extension, as they can mimic the neural tissue extra cellular matrix (ECM) and combine the advantages of the combinatorial therapy for nerve injury in SCI cases. In this work, we aimed to fabricate a nanostructured scaffold that can be used as a physical support for maintaining axonal growth and regeneration in the lesion site and provide the suitable environment for axonal extension to reconnect with their target neurons and restore their functional recovery. Characterization techniques such as Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), and Fourier transform infrared spectroscopy (FTIR) were done and the material was optimized to mimic the properties of the natural environment of the neural tissue in terms of biological and architectural properties. The results revealed that the material does mimic the properties of the neural tissues and can be considered a regenerative treatment for SCI.